2018
DOI: 10.1097/bpb.0000000000000516
|View full text |Cite
|
Sign up to set email alerts
|

The reliability of radiostereometric analysis in determining physeal motion in slipped capital femoral epiphysis in standard uniplanar and low-dose EOS biplanar radiography: a phantom model study

Abstract: Physeal closure after slipped capital femoral epiphysis fixation can be difficult to assess on two-dimensional conventional radiographs. Radiostereometric analysis offers improved motion detection over conventional radiography, whereas the EOS biplanar imager provides a means for low radiation weight-bearing images. This phantom study assessed the reliability of measuring motion using radiostereometric analysis in the EOS using a slipped capital femoral epiphysis model. The accuracy and precision were better t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The EOS imager provides registered biplanar images and does not need a reference object in every scan [ 14 ] due to the built-in registration of the AP and lateral images. This study has demonstrated similar precision to the standard suite using only a once-a-month calibration of the system geometry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EOS imager provides registered biplanar images and does not need a reference object in every scan [ 14 ] due to the built-in registration of the AP and lateral images. This study has demonstrated similar precision to the standard suite using only a once-a-month calibration of the system geometry.…”
Section: Discussionmentioning
confidence: 99%
“…The EOS imaging technology has a larger pixel size than current digital RSA systems and the vertical translation of its scanning X-ray head may impact the accuracy and precision of the RSA technique. A phantom study has demonstrated that RSA on EOS images is technically feasible [ 14 ], but to date no in vivo precision has been published.…”
mentioning
confidence: 99%
“…As the EOS imaging system offers comparable accuracy to that of radiostereometric analysis in terms of angular measurements 55 , it may be reasonable to assume that the major source of errors is manual registration of anatomical landmarks 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that adults who break their femur and are not already interned in a hospital or in the hospital may require special care for one year in a proportion of 25% of the cases (Kral et al, 2018;Sheikh et al, 2018;Qureshi et al, 2018). They are usually diagnosed based on objective examination and bone radiography (Hurry et al, 2018). The signs of the femur fracture include the strong pain, the inferior limb shorter than the unaffected and external rotation of the femur.…”
Section: Introductionmentioning
confidence: 99%